Ethics for the information age - Quinn, Michael J. (Michael Jay) (Pearson Education/Addison-Wesley, 2013)
In an era where IT changes constantly, a thoughtful response to these rapid changes requires a basic understanding of IT history, an awareness of current issues, and a familiarity with ethics. This book provides an overview of ethical theories and problems encountered by computer professionals in today's environment.